PRELIMINARY STUDY OF WATER INJECTION ON THE COMBUSTION AND EMISSIONS CHARACTERISTICS IN A HCCI ETHANOL ENGINE - Telli, G. D.; Zulian, G. Y.; Stefanello, S. R.; Lanzanova, T. D. M.; Martins, M. E. S.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2020)
Our dependence on fossil fuels coupled with concerns about harmful emissions have motivated researchers to look for renewable fuels that have clean combustion and for advanced combustion modes. In this context, homogeneous charge compression ignition (HCCI) is an emerging technology which offers an alternative to conventional spark ignition and compression ignition engines and can operate on renewable fuels. Low temperature combustion, which can result in low NOx emissions with high indicated efficiency, is the more important characteristic of this combustion mode. It’s main problem is the combustion timing control due to lack of direct ignition control, once HCCI flame initiation is based on charge thermal state. Thus, controlled auto-ignition (CAI) combustion mode has been proposed. Several methods were proposed for combustion phasing control, between them, the injection of water in the intake manifold. This work investigated the influence of water injection in the intake runner of an ethanol HCCI cylinder from a converted three-cylinder diesel generator set, in which two cylinders operated on conventional diesel combustion and one diesel cylinder provided recycled exhaust gas for the one cylinder running on ethanol HCCI combustion. The water injection was used to control the CA50 combustion parameter. The results show that water injection is an efficient strategy to control the combustion timing, since the reactivity of the mixture can be controlled. The results at 400 and 600 kPa of IMEP and 1800 rpm indicated a good combustion stability, high efficiency and low emissions characteristics. The highest indicated fuel conversion efficiency found was 36.9% for 600 kPa of IMEP and 8 CAD of CA50. However, for 200 kPa of IMEP the combustion was unstable, the indicated efficiency was deteriorated and indicted CO emissions was high.